2008
DOI: 10.1080/02699050801935245
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life and psychosocial consequences after mild traumatic brain injury in children and adolescents

Abstract: Mild TBI resulted in no decline in the children's health outcome after injury. The cognitive screening approach proved itself to be a useful instrument for routine clinical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 17 publications
3
27
2
Order By: Relevance
“…However, two recent longitudinal investigations conducted in New Zealand and Germany, respectively, concluded that TBI is not likely to cause neurocognitive impairment in children and adolescent (18,19). The discrepancy between our study and these two investigations may be explained by differences in study designs and the environmental characteristics of the target populations.…”
Section: Articlescontrasting
confidence: 54%
See 1 more Smart Citation
“…However, two recent longitudinal investigations conducted in New Zealand and Germany, respectively, concluded that TBI is not likely to cause neurocognitive impairment in children and adolescent (18,19). The discrepancy between our study and these two investigations may be explained by differences in study designs and the environmental characteristics of the target populations.…”
Section: Articlescontrasting
confidence: 54%
“…A longitudinal birth cohort study reported no association between preschool mild TBI and ADHD after adjusting for potential covariates (18). Nevertheless, a prospective cohort study reported that children with mild TBI have a higher risk of hyperactivity in the first year after injury (19). Nevertheless, a prospective cohort study reported children with mild TBI were associated higher risk for hyperactivity in the first year after injury (20).…”
mentioning
confidence: 95%
“…First results of one setting have already been reported [22]. This study reports cognitive impairment in different patient groups and a healthy control group.…”
Section: Introductionmentioning
confidence: 62%
“…As suggested by several studies on older post-TBI children and adolescents [4,5,[9][10][11], these subjects showed more marked Externalizing problems (in particular, destructive behaviour). The prevalence of this group of disorders is related to the neuroradiological picture and in particular to the presence of frontal damage.…”
Section: Discussionmentioning
confidence: 89%
“…In most cases, acquired brain lesions do not only determine motor, sensory and neuropsychological impairments but also psychological and behavioural disorders [1][2][3][4][5]. The latter should be closely monitored because they can significantly affect the overall outcome.…”
Section: Introductionmentioning
confidence: 96%